Does AI work for us, or do we work for AI? The Reverse Centaur’s Guide to Life After AI Cory Doctorow MCD, 2026. 240 pp. - Timothy Wu (Science, 2026)
There is little enthusiasm for a technology that turns human users into “reverse centaurs,” argues a critic